The Moderating Effect of Learning Experience on Learning Motivation and Learning Outcomes of International Students - Zhang, Jingxiao; Sun, Gangzhu; Xu, Lin; Khan, Inayat; Lv, Weidong; Philbin, Simon P. (Frontiers in Psychology, 2022)
With the increasing level of internationalization in higher education, the number of international students in mainland China is rapidly increasing. However, limited research has considered that student results may be affected by a reduced motivation to learn. Therefore, the aim of this research is to explore the effect of the learning motivation on the learning outcomes of international students and the moderating role of learning experience. A sample of 130 international students from 23 countries studying in mainland China was analysed. The study found a significant correlation between the learning motivations and international students’ learning outcomes. It was also determined that learning experience has significantly enhances the relationship between learning motivation and the learning outcomes of international students. This study contributes to the higher education literature of on learning motivation by students and learning outcomes.